Complete hydatidiform mole in Hospital Universiti Sains Malaysia Kubang Kerian Kelantan: A review of 120 cases (January 1983-December 1992) - Abdullah, Ab.Rahman (1995)
Hydatidiform mole, invasive mole, and choriocarcinoma are neoplasms that originate in the fetal chorion. According to Hertz (1), the benign hydatidiform mole represents the beginning of a disease continuum, whereas the highly malignant choriocarcinoma represents the end of the spectrum. It has been known for many years that most hydatidiform moles are female. In a collected series of hydatiform mole sex chromatin studies, Lawler (2) reported a 90% overall frequency of chromatin-positive cases. The remaining 10% of the cases were assumed to be male. In 1978 Szulman and Surti (3) reported that hydatidiform moles could be divided into two distinct syndromes. They described the complete or classic mole without discernable embryo or fetus and with diploid karyotype, and the partial mole in which there was an ascertainable fetus and a triploid karyotype. Complete moles appeared clinically as missed abortions usually during the second trimester, whereas partial moles presented in the first trimester or rarely as spontaneous abortions. The incidence of gestational trophoblastic disease appears to vary widely in different parts of the world. In the United Kingdom hydatidiform moles occur as a complication of approximately 1 in 1500 pregnancies while in in Indonesia estimates are of the order of 1 in 200 pregnancies (4) .